2022
DOI: 10.3389/fpls.2022.978299
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal patterns and environmental drivers of taxonomic, functional, and phylogenetic diversity of woody plants in western Amazonian terra firme forests

Abstract: Elucidating how environmental factors drive plant species distributions and how they affect latitudinal diversity gradients, remain essential questions in ecology and biogeography. In this study we aimed: 1) to investigate the relationships between all three diversity attributes, i.e., taxonomic diversity (TD), functional diversity (FD), and phylogenetic diversity (PD); 2) to quantify the latitudinal variation in these diversity attributes in western Amazonian terra firme forests; and 3) to understand how clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 104 publications
(167 reference statements)
0
5
0
Order By: Relevance
“…Our study showed latitudinal changes in soils properties, with an increase in soil fertility and a decrease in pH towards the Equator (Figure S1;Ben Saadi et al, 2022). These properties affect the species diversity, performance and composition at local scales (Bañares- de-Dios et al, 2022).…”
Section: Variations In Species Diversity and Composition With Latitud...mentioning
confidence: 76%
See 3 more Smart Citations
“…Our study showed latitudinal changes in soils properties, with an increase in soil fertility and a decrease in pH towards the Equator (Figure S1;Ben Saadi et al, 2022). These properties affect the species diversity, performance and composition at local scales (Bañares- de-Dios et al, 2022).…”
Section: Variations In Species Diversity and Composition With Latitud...mentioning
confidence: 76%
“…A higher ecosystem productivity results in higher speciation, and ability to maintain species in the ecosystem (Loreau, 2000), resulting in lower extinction rates (Brown, 2014). Our study showed latitudinal changes in soils properties, with an increase in soil fertility and a decrease in pH towards the Equator (Figure S1;Ben Saadi et al, 2022). These properties affect the species diversity, performance and composition at local scales (Bañares- de-Dios et al, 2022).…”
Section: Variations In Species Diversity and Composition With Latitud...mentioning
confidence: 76%
See 2 more Smart Citations
“…This result aligns with previous evidence showing that vegetation structure and climate play a key role in explaining patterns of biodiversity facets at both global and regional scales (Feng et al., 2020 ; Prescott et al., 2016 ; Rurangwa et al., 2021 ), including bryophytes (Chen et al., 2017 ; Collart et al., 2024 ; Ilić et al., 2023 ; Mežaka et al., 2012 ; Shen et al., 2023 ). At the local scale, environmental filtering associated with elevation, climate, and habitat structure played a more important role in shaping α‐ and β‐components of TD, FD, and PD in bryophytes (Araújo et al., 2022 ; Chen et al., 2017 ) and spermatophytes (Ben Saadi et al., 2022 ; Culmsee & Leuschner, 2013 ). On Madeira Island, both precipitation and vegetation are strongly determined by elevation and slope at the local scale (Capelo et al., 2005 ; Sim‐Sim et al., 2014 ), a situation that reinforces the role of these ecological drivers on the three facets of α‐ and β‐diversities and community assembly.…”
Section: Discussionmentioning
confidence: 99%